2015
DOI: 10.1517/14740338.2015.1059817
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events associated with somatostatin analogs in acromegaly

Abstract: On the basis of these findings, a close and careful monitoring of gallbladder ultrasound and glucose levels is recommended in patients receiving SSA for medical treatment of acromegaly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 104 publications
(140 reference statements)
2
35
2
2
Order By: Relevance
“…Other retrospective studies based on patients with NENs reported a prevalence of 52%–63%, but studies on this specific population are few . On the contrary, many studies on patients receiving SSAs to treat acromegaly are available, reporting a very variable biliary stone frequency (3%–56% in the first 2 years of treatment) . However, patients with acromegaly are not comparable to those with NETs, because acromegaly has already been identified as a risk factor for gallstones occurrence per se .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other retrospective studies based on patients with NENs reported a prevalence of 52%–63%, but studies on this specific population are few . On the contrary, many studies on patients receiving SSAs to treat acromegaly are available, reporting a very variable biliary stone frequency (3%–56% in the first 2 years of treatment) . However, patients with acromegaly are not comparable to those with NETs, because acromegaly has already been identified as a risk factor for gallstones occurrence per se .…”
Section: Discussionmentioning
confidence: 99%
“…The role of SSAs in the pathogenesis of gallstone disease is related to several factors. First, SSAs tend to inhibit meal‐stimulated cholecystokinin release, resulting in reduced gallbladder motility . In addition, SSAs slow intestinal transit, allowing intestinal bacteria to increase the amounts of deoxycholate, which favors the aggregation of cholesterol crystals into stones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cholelithiasis represents the most serious complication of SSAs, but is generally asymptomatic, and has been reported in 3-56% of patients. Pasireotide has shown a safety profile as expected for an SSA, except for the degree of hyperglycemia [189]. Uncommon side effects include sinus bradycardia, asthenia, headache, pruritus, decreased libido, increased serum bilirubin, and constipation [190].…”
Section: Adverse Eventsmentioning
confidence: 97%
“…LA-SSAs suppress GH secretion by preferential binding to somatostatin receptor subtype 2a (SSTR2a). LA-SSAs have favorable safety profiles and a clinically neutral impact on glucose homeostasis (4,5). In clinical practice only about 40% of patients treated with monotherapy LA-SSAs achieve biochemical normalization of GH and IGF-I.…”
Section: Introductionmentioning
confidence: 99%